Mulheres do campo, reconhecimento e trabalho na construção de outras economias em Porteirinha - MG - Daniela Mendes Queiroz (2018)
This work consists of analyzing the trajectory of women, especially rural women. Bordieu's approaches were used to portray the oppressive system experienced throughout history, appropriating male domination to analyze symbolic power. Empowerment is related to the conceptions of Alain Touraine, who analyzes subjects and their subjectivities in the construction of individual and collective identity. The central objective of the study was to investigate the involvement and organization of women in activities / work as a possibility to break male domination. The method used was exploratory research, participant observation and semi-structured questionnaire. The field of study was the Municipality of Porteirinha - MG, with information collected in the communities of Bom Jesus and Paraguay, Rural Workers' Union and Feirinha da Semana. The results of the research showed the importance of collective organization to break with the stigmas perpetuated mainly by institutions such as the state, the school and the church. Contemporary social movements present themselves as "networks of solidarity" with cultural connotations capable of strengthening the assimilation of new languages and values. The feminist movement, despite the philosophical and political influence portrayed in the struggle for gender equality, presents itself as a preponderant factor for the convergence of "micro" issues, located in the sphere of subjectivity and the private sphere, and this is directly related to the conquests related to policies for women. The agroecological movement, agroecological fairs and Rural Workers' Unions are spaces conducive to the social, cultural and political empowerment of women who use routine and daily activities to break the "invisibility" barriers. There is evidence of the existence of public policies and even organizations that seek to assist women in the process of empowerment. A look at the rural women's movements leaves clear the process of transformation, both in its organizational form and in public performance. Various movements, representing diverse social and political identities, emerged in the public space, through actions and mobilizations that, as they grew, gave visibility to rural women.